2014
DOI: 10.1590/1678-6809
|View full text |Cite
|
Sign up to set email alerts
|

Genes de virulência e diversidade genética em Salmonella spp. isoladas de amostras de origem suína

Abstract: RESUMOA diversificação da produção industrial de alimentos de origem suína e o intercâmbio comercial de animais e seus derivados destinados ao consumo humano podem ser importantes disseminadores de sorovares de Salmonella spp. na cadeia alimentar. Objetivou-se avaliar em 86 cepas de Salmonella spp., isoladas em granja de terminação e no abate de suínos, a ocorrência de três genes de virulência (invA, agfA e lpfA), bem como a similaridade genética entre elas. A ocorrência do gene invA foi verificada em 100% das… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…There were also signs of neglect of biosecurity standards in the food industry environment due to the presence of the agent in clean and dirty processing areas. According to Moura et al [ 43 ], this oversight is decisive in the maintenance of the microorganism in the environment. At the same time, pulsotype K indicated that there was spread of this profile, since there were similar strains in Mato Grosso do Sul and Minas Gerais, Brazil, in different slaughter units.…”
Section: Resultsmentioning
confidence: 99%
“…There were also signs of neglect of biosecurity standards in the food industry environment due to the presence of the agent in clean and dirty processing areas. According to Moura et al [ 43 ], this oversight is decisive in the maintenance of the microorganism in the environment. At the same time, pulsotype K indicated that there was spread of this profile, since there were similar strains in Mato Grosso do Sul and Minas Gerais, Brazil, in different slaughter units.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is necessary to establish more efficient and rigorous hygiene and biosafety measures to guarantee the control of this agent in the aviary's environment. According to Moura et al (2014) the neglecting of biosecurity standards within the industry is a decisive factor for the maintenance of the microorganism in the environment.…”
Section: Resultsmentioning
confidence: 99%
“…In the following steps such as handling, packaging, storage and transport of animal meal at room temperature, there were risks of contamination and recontamination by microorganisms that were distributed in the industry environment. It is important to consider that these studies were carried out in greases that used as raw material by-products generated from slaughtering under inspection of animal products (federal, state or municipal) (Larsen et al, 2014;Maciorowski et al, 2007;Melo et al, 2011;Moura et al, 2014;Pellegrini et al, 2015). In the European Union, Larsen et al (2014) reported a decrease in the presence of Salmonella from 0.7% to 0.5% in the diet and from 2.9% to 0.6% in meat and bone meal between 2002 and 2010.…”
Section: Resultsmentioning
confidence: 99%